2010
DOI: 10.1002/jcp.22070
|View full text |Cite
|
Sign up to set email alerts
|

Non‐genomic rapid inhibition of Na+/H+‐exchange 1 and apoptotic immunosuppression in human T cells by glucocorticoids

Abstract: Glucocorticoids (GCs) have been employed as immunosuppressive agents for many years. However, it is still unclear how GCs instantly uncouple T cells from acute stressful inflammatory. In terms of time scale, the genomic activity of the classic GC receptor cannot fulfill this role under crisis; but a rapid non-genomic response can. In a previous study, intracellular acidification was found to be due to a rapid non-genomic inhibition of Na(+)/H(+)-exchange 1 (NHE1) and this event led to the immunosuppression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
3
10
0
1
Order By: Relevance
“…Previously, it was suggested that IL-2 signaling could induce NHE1 activity in human T cells (51) as well as in murine T cells (52,53). In extension to these previous findings, our study revealed that each Th cell subset differs in pH i , which is governed by Na ϩ /H ϩ exchanger activity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previously, it was suggested that IL-2 signaling could induce NHE1 activity in human T cells (51) as well as in murine T cells (52,53). In extension to these previous findings, our study revealed that each Th cell subset differs in pH i , which is governed by Na ϩ /H ϩ exchanger activity.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies in human T cells have suggested that addition of IL-2 to cultured cells could enhance pH i and NHE1 protein abundance, thus affecting cell proliferation, cytokine production, and apoptosis (51). It has been further proposed that pH i and NHE1 activity are modulated by glucocorticoids in a non-genomic fashion (49,(52)(53)(54)(55)(56). However, to which extent pH i and NHE activity govern Th9 cell development and function is incompletely understood.…”
Section: Cd4mentioning
confidence: 99%
“…At least for one of its interactors, the G-protein coupled protein receptor ADRB2 nuclear localization has been shown in the hippocampus [48]. NHERF1 also interacts with Na(+)/H(+)-exchanger 1 (NHE1), an ion transporter that has been shown to be inhibited by rapid non-genomic effects of GC leading to immunosuppression in T cells [49]. This interaction is also interesting since NHE1 has been recently identified as a MAPK scaffold [50].…”
Section: Discussionmentioning
confidence: 94%
“…For example, in activated murine thymocytes GCs inhibited the activation of Na + -K + -ATPase and Ca 2+ -ATPase (Buttgereit and Scheffold, 2002), and the Na + /H + exchange could also be inhibited with GCs (Chang et al, 2010). Membrane GR expression has been observed first in the S-49 mouse T lymphoma cells and the CCRF-CEM human T cell lymphoblast like cell line, and later on human peripheral lymphocytes and monocytes; however, its exact structure and signaling mechanisms are still unclear (Gametchu et al, 1993).…”
Section: Introductionmentioning
confidence: 98%